Ethics of luxury dining - Sayson, Maxine Beatrice Vinaviles (Animo Repository, 2024)
There has recently been a surge in gourmet food and luxury dining establishments. Due to social media and influencers, more people have gained interest in partaking in these experiences. However, we can see there are ethical implications such as environmental impact and exploitation of labor in these luxury restaurants and yet little literature surrounding the ethics of it. In this paper, I first introduced luxury, luxury fashion, and luxury dining. Then I moved onto the philosophical perspective on luxury, discussing the ongoing debates and discussions in both areas. As for my framework, I used Arne Naess and George Sessions’ Deep Ecology wherein I highlighted two points out of the eight to be used as our criteria. Afterwards, I moved onto luxury dining and its practices, highlighting the problematic practices unique only to luxury dining. To argue for my paper, I ethically analyzed the unique and problematic practices of luxury dining and critiqued them using Deep Ecology. By examining the practices and issues present within Luxury Dining, the paper has identified which practices directly damage the environment. The purpose of this is to introduce and start the discussion of philosophy in luxury dining with regards to environmental ethics. This paper claimed that the practices in Luxury Dining causes negative environmental impact. Thus, this paper explored Luxury Dining practices and its environmental impacts that are inconsistent with the points of Deep Ecology.